1995
DOI: 10.1007/bf02065554
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intestinal inflammation (IBD) and small and large bowel length on fecal short-chain fatty acids and lactate

Abstract: Treatment with short-chain fatty acids (SCFAs) seems promising in ulcerative colitis and changes in colonocyte oxidation of butyrate have been suggested to be of importance for the development of this disease. The influence of small and large bowel length after surgery on SCFAs is only partly known. SCFAs and lactate were measured in consecutive fecal samples from 300 patients with ulcerative colitis (103), Crohn's disease (127), and noninflammatory bowel disease (70); 205 had had surgery, 52 had short bowels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 31 publications
7
47
0
2
Order By: Relevance
“…[86][87][88] As a consequence, luminal butyrate concentrations are expected to drop in patients with IBD. However, as reported above, luminal butyrate concentrations have been reported increased 78 or unchanged 79 in IBD patients. Therefore, changes in butyrate-producing intestinal microflora could affect the colonic mucosa homeostasis independently of butyrate.…”
Section: Changes In Luminal Butyrate Concentrations and Phmentioning
confidence: 69%
See 1 more Smart Citation
“…[86][87][88] As a consequence, luminal butyrate concentrations are expected to drop in patients with IBD. However, as reported above, luminal butyrate concentrations have been reported increased 78 or unchanged 79 in IBD patients. Therefore, changes in butyrate-producing intestinal microflora could affect the colonic mucosa homeostasis independently of butyrate.…”
Section: Changes In Luminal Butyrate Concentrations and Phmentioning
confidence: 69%
“…77 In children with UC and CD, Treem et al 78 reported raised fecal concentrations of butyrate, but decreased acetate concentrations as compared with age-matched controls. Hove and Mortensen 79 found no correlation between SCFA fecal concentrations and localization or activity of intestinal inflammation in either UC or CD. Overall, the results of these studies are contradictory and do not allow drawing conclusions about changes in butyrate concentrations in the colonic lumen of patients with active IBD.…”
Section: Changes In Luminal Butyrate Concentrations and Phmentioning
confidence: 98%
“…In human healthy adults, no or low (0 -2 mM) lactate is detected in fecal samples (50,51) because the luminal lactate is absorbed by host and is also used as an energy source by other commensal bacteria (52)(53)(54). However, increased fecal lactate has been associated with intestinal malabsorption and colitis (55). It could also be of interest to measure fecal lactate in humans with short bowel syndrome because we have shown that their microbiota is deeply enriched in lactobacilli at the expense of other bacterial members (22).…”
Section: Discussionmentioning
confidence: 99%
“…(23) Quanto a outros aspectos funcionais, sabe-se que os ácidos graxos de cadeia curta aumentam absorção de água e de sódio da luz intestinal. (24,25) Estudos experimentais imputaram à glicose hipertônica, fatores positivos na cicatrização de anastomoses. (19) Outras pesquisas em ratos concluíram que instilação de soluções com concentração elevada de glicose na luz do colo apresenta efeito protetor quanto a prevenção do aparecimento de neoplasias.…”
Section: Infiltrado Inflamatóriounclassified